Interobserver Agreement for Mismatch Repair Protein Immunohistochemistry in Endometrial and Nonserous, Nonmucinous Ovarian Carcinomas. (May 2019) - Sari, Aysegul; Pollett, Aaron; Eiriksson, Lua R.; Lumsden-Johanson, Brenda; Van de Laar, Emily; Kazerouni, Hamid; Salehi, Amir; Sur, Monalisa; Lytwyn, Alice; Ferguson, Sarah E.
Abstract : Immunohistochemistry (IHC) for mismatch repair (MMR) proteins is an established test to identify Lynch syndrome (LS) in patients with colorectal cancer and is being increasingly used to identify LS in women with endometrial and/or nonserous ovarian cancer (OC). We assessed interobserver agreement in the interpretation of MMR-IHC on endometrial and ovarian carcinomas. The study consisted of 73 consecutive endometrial cancers (n=48) and nonserous, nonmucinous epithelial OCs (n=25). Six pathologists from 2 cancer centers, one with and the other without, previous experience in interpreting MMR-IHC, evaluated MLH1, MSH2, MSH6, and PMS2 stains. Before the study, an experienced pathologist led a review of 9 teaching cases. A decision tool was developed as a guide in MMR-IHC interpretation. Staining was interpreted as intact, deficient, or equivocal for each protein. Interobserver agreement for the patient MMR status was categorized as "almost perfect" with κ=0.919 (95% CI, 0.863-0.976). All observers were in agreement in 66 (92%) tumors. Four of the less experienced pathologists had at least 1 discrepant interpretation. There were 6 discordant cases: 3 MMR-deficient cases and 2 MMR-intact cases by majority opinion were called equivocal by at least 1 observer, and 1 MMR-deficient case by majority opinion was interpreted as MMR intact by 1 pathologist. Only the latter case (1/73 patients, 1.4%) had an unequivocal disagreement that could affect patient management. Issues associated with discordant interpretation included heterogeneous staining, intratumoral lymphocytes, regional reduced internal control tissue staining, and scattered absent/weak staining adjacent to tumor cells with strong nuclear staining. Abstract : Supplemental Digital Content is available in the text.